Change in the Foveal Avascular Zone and Macular Capillary Network Density after Hyperbaric Oxygen Therapy in Healthy Retina - Sadık Görkem Çevik; Bekir Selim Bağlı (Journal of Ophthalmic & Vision Research)
Abstract Purpose: This study aimed to evaluate responses in retinal tissue by swept source OCT angiography (OCT-A) to hyperoxia after hyperbaric oxygen (HBO2) therapy. Methods: The study was conducted in volunteers who received HBO2 treatment but did not have any eye disease. Patients underwent detailed eye examinations including dilated fundus examination, visual acuity, and refraction before being admitted for HBO2 therapy. Measurements were made before and immediately after HBO2 therapy. Enface images of the retinal vasculature were obtained from the superficial and deep retinal plexus (SP/DP). Quantitative analysis of the vessel density (VD) and foveal avascular zone (FAZ) area was performed. Results: In total, 31 patients (15 female) with healthy retina were included in the study. The mean age was 42.8 years. The mean SP vascular density measurements before HBO2 therapy for the right and left eyes were 15.18 ± 1.2 mm - 1 and 15.01 ± 1.3 mm - 1 , respectively; the measurements after HBO2 therapy for the right and left eyes were 14.34 ± 1.4 mm - 1 and 14.48 ± 1.19 mm - 1 . The mean DP vascular density measurements before HBO2 therapy for the right and left eyes were 16.03 ± 1.69 mm - 1 and 16.1 ± 1.45 mm - 1 , respectively; the measurements after HBO2 therapy for the right and left eyes were 15.02 ± 1.65 mm - 1 and 15.12 ± 2.16 mm - 1 , respectively. Reduction of mean VD in superficial and deep plexus after HBO2 was statistically significant (P = 0.001 and P = 0.000, respectively). Changes in mean FAZ area before and after HBO2 therapy were not statistically significant (P = 0.719). Conclusion: The healthy retina responds to oxygen supersaturation with HBO2 therapy by eventually decreasing vascular density in all layers. These findings may be important for further studies especially related to retina and choroidal oxygenation.